2022
DOI: 10.3389/fpubh.2021.723252
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Child Mortality at the Sub-national Level in Papua New Guinea: Evidence From the Integrated Health and Demographic Surveillance System

Abstract: BackgroundChild mortality is an important indication of an effective public health system. Data sources available for the estimation of child mortality in Papua New Guinea (PNG) are limited.ObjectiveThe objective of this study was to provide child mortality estimates at the sub-national level in PNG using new data from the integrated Health and Demographic Surveillance System (iHDSS).MethodUsing direct estimation and indirect estimation methods, household vital statistics and maternal birth history data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…14 In light of other literature from national census data, the under-five mortality trajectory in the Solomon Islands showed a decline from 38 to 21/1000 live births between 1990 and 2015. 15 , 22 , 23 Our estimated under-five mortality is lower than Sub Saharan countries of Africa 24 , 25 and PNG, 26 however it was still higher than some countries of the Polynesia region, 27 which signified that under-five mortality remains a public health problem for the Solomon Islands.…”
Section: Discussionmentioning
confidence: 85%
“…14 In light of other literature from national census data, the under-five mortality trajectory in the Solomon Islands showed a decline from 38 to 21/1000 live births between 1990 and 2015. 15 , 22 , 23 Our estimated under-five mortality is lower than Sub Saharan countries of Africa 24 , 25 and PNG, 26 however it was still higher than some countries of the Polynesia region, 27 which signified that under-five mortality remains a public health problem for the Solomon Islands.…”
Section: Discussionmentioning
confidence: 85%
“…They identified deaths through home visits, reported deaths to surveillance team leaders and pre-arranged VA interviews at a time and location convenient for the participants. 18 VA interviews were often conducted in Pidgin and Motu languages and by national scientific officers, who were based in the CHESS field offices. Some VA interviews required more than one home visit to complete.…”
Section: Methodsmentioning
confidence: 99%
“…CHESS was designed as a population-based longitudinal follow-up cohort study, with an aim to provide up-to-date data series for monitoring and evaluation of the impact of socioeconomic development programmes and health interventions on the health of the population at the national and subnational levels. The design and methods of CHESS have been published elsewhere 16–18…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Child mortality remains higher in the developing world compared to the developed world. Pham et al ( 2 ), using the integrated Health and Demographic Surveillance System (iHDSS), estimated child mortality at the sub-national level in Papua New Guinea. The authors concluded that contextual factors such as women's fertility, childhood communicable diseases, and immunization services could have a critical role in explaining the variations in child mortality.…”
Section: Contribution To the Fieldmentioning
confidence: 99%